(untitled) (Estudios Sociales, 2022)
This work studies the trajectory of Juan Carlos Agulla, reconstructing his spaces of intellectual socialization and sociological production until 1966. In this journey, a strong theoretical imprint of Weberian sociology is appreciated, product of his training in Germany, at the same time as the influence of other traditions such as the functionalism of Talcott Parsons and Robert Merton. In turn, his study stay at FLACSO (Chile), where he established ties with José Medina Echavarría, was an important moment for acquiring knowledge about modern sociological methodologies that enabled him, together with Eva Chamorro and Delbert C. Miller, to carry out a pioneering research on the power structure of his native city, thus founding the empirical sociology at the National University of Córdoba.